RESILIENCE IN REMOTE ECONOMIES: EXTERNAL CHALLENGES AND INTERNAL ECONOMIC STRUCTURE - Huskey, Lee (The journal of contemporary issues in business and government, 2011)
This paper presents a model that emphasises the role of an economy’s internal structure in its response to external challenges. The model is an extension of Thompson’s "urban size ratchet" to small, remote economies. Thompson’s model suggests the internal structure of economies provides the mechanism of response to external challenges. A number of case studies from Alaska communities show how this mechanism has worked. The goal of the paper is to see if these stories are consistent with the general idea that resilience can be explained by a community’s internal structure.